2022
DOI: 10.3390/ijms23052810
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in Schizophrenia: The Key Role of the WNT/β-Catenin Pathway

Abstract: Schizophrenia is a very complex syndrome involving widespread brain multi-dysconnectivity. Schizophrenia is marked by cognitive, behavioral, and emotional dysregulations. Recent studies suggest that inflammation in the central nervous system (CNS) and immune dysfunction could have a role in the pathogenesis of schizophrenia. This hypothesis is supported by immunogenetic evidence, and a higher incidence rate of autoimmune diseases in patients with schizophrenia. The dysregulation of the WNT/β-catenin pathway is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 163 publications
(191 reference statements)
1
30
0
Order By: Relevance
“…Our previous study demonstrated that Cd 2+ induces microglia activation and neuroinflammation in the brains of zebrafish larvae. Given that the Wnt signaling pathway has been reported to significantly regulate neuroinflammatory responses [ 49 ], we, thus, investigated the role of this pathway in Cd 2+ -induced microgliosis and neuroinflammation. Through in vivo two-photon imaging of the microglia-specific Tg(ApoE: EGFP) transgenic line, we observed and verified that upon Cd 2+ exposure, the microglia in the brain of zebrafish larvae showed distinct branch retraction, changing their morphology from ramified to amoeboid, which is a typical morphological change of microglia activation and neuroimmune response.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that Cd 2+ induces microglia activation and neuroinflammation in the brains of zebrafish larvae. Given that the Wnt signaling pathway has been reported to significantly regulate neuroinflammatory responses [ 49 ], we, thus, investigated the role of this pathway in Cd 2+ -induced microgliosis and neuroinflammation. Through in vivo two-photon imaging of the microglia-specific Tg(ApoE: EGFP) transgenic line, we observed and verified that upon Cd 2+ exposure, the microglia in the brain of zebrafish larvae showed distinct branch retraction, changing their morphology from ramified to amoeboid, which is a typical morphological change of microglia activation and neuroimmune response.…”
Section: Resultsmentioning
confidence: 99%
“…It has been evidenced that neuroinflammation mediated by the NF-κB and related pathways plays a role in the pathogenesis of schizophrenia (Murphy et al, 2021 ; Vallée, 2022 ). Using an MIA model, this study provided the first evidence that epigenetic histone acetylation of H3 and H4 (H3ace and H4ace, respectively) peaking on the promoter region of Rela was involved in the activation of the NF-κB mediated inflammatory pathway in the PFC induced by prenatal Poly I:C exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation in the central nervous system, particularly the prefrontal cortex (PFC), is involved in the pathogenesis of schizophrenia, in which the nuclear factor kappa-B (NF-κB) and related pathways play an important role (Murphy et al, 2021 ; Vallée, 2022 ). Exposure to polyriboinosinic-polyribocytidylic acid (Poly I:C), a mimic of viral dsRNA, during a specific period of pregnancy is one of the commonly used animal models for studying the pathogenesis of MIA-induced neuropsychiatric disorders, including schizophrenia and autism (Reisinger et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…These cytokines serve to contain and resolve the inflammatory foci through activation of local and systemic inflammatory responses. Pro-inflammatory cytokines may directly modulate neuronal activity in various classes of neurons in CNS, including dopaminergic neurons [ 97 ]. The major pro-inflammatory cytokines that are responsible for early responses are interleukin 1 alpha (IL1-α), interleukin 1 β (IL1-β), interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α).…”
Section: Cytokines Alteration In Treatment-resistant Schizophreniamentioning
confidence: 99%